Investigation of the barrier options pricing models - Palivonaitė, Rita; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2009)
In the article three methods of barrier option pricing are analysed and compared: Black–Scholes, trinomial ant adaptive mesh algorithm. Investigation with Lithuanian firm’s stock showed, that to get better results it is offered to adapt higer resolution mesh on critical regions of trinomial tree.